2012
DOI: 10.1111/j.1582-4934.2011.01455.x
|View full text |Cite
|
Sign up to set email alerts
|

Human versus porcine mesenchymal stromal cells: phenotype, differentiation potential, immunomodulation and cardiac improvement after transplantation

Abstract: Although mesenchymal stromal cells (MSCs) have been applied clinically to treat cardiac diseases, it is unclear how and to which extent transplanted MSCs exert their beneficial effects. To address these questions, pre-clinical MSC administrations are needed for which pigs appear to be the species of choice. This requires the use of porcine cells to prevent immune rejection. However, it is currently unknown to what extent porcine MSCs (pMSCs) resemble human MSCs (hMSCs). Aim of this study was to compare MSC fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
88
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 50 publications
18
88
0
3
Order By: Relevance
“…In this regard, the CD34-positive but CD117/c-kit negative phenotype we found in this study can indicate rejection of an endothelial tip cell diagnosis, HSCs being already rejected when the stromal compartment is observed. This reinforces a mesenchymal stem/progenitor phenotype of the stromal mammary fibroblastoid cells we studied, which is supported by recent experiments in which TCs were found positive for CD29 [3], a known MSCs marker [26,46].…”
Section: Discussionsupporting
confidence: 63%
“…In this regard, the CD34-positive but CD117/c-kit negative phenotype we found in this study can indicate rejection of an endothelial tip cell diagnosis, HSCs being already rejected when the stromal compartment is observed. This reinforces a mesenchymal stem/progenitor phenotype of the stromal mammary fibroblastoid cells we studied, which is supported by recent experiments in which TCs were found positive for CD29 [3], a known MSCs marker [26,46].…”
Section: Discussionsupporting
confidence: 63%
“…MSCs isolated from different tissues of pigs robustly express CD 90 (54,(62)(63)(64) and CD 105 (54). CD 73 investigation in pig is hampered by a lack of cross-reactive mAbs (63).…”
Section: Discussionmentioning
confidence: 99%
“…This work is motivated by similar studies performed using MSC, which have been shown to improve cardiac function when injected into the heart post-MI. [59][60][61][62] A summary of AFSC implantation studies and results can be found in Table 4.…”
Section: Implantation Of Afsc After Myocardial Infarctmentioning
confidence: 99%